Looking Through the Wound: The Photographic Turn of Protest from the Military Dictatorship to the Popular Uprising in Chile; [Mirar por la Herida.El Giro Fotográfico de la Denuncia Desde la Dictadura Militar a la Revuelta Popular en Chile] - Shuffer-Mendoza, C (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2024)
It is possible to observe a continuity in the violence directed against those who sought to challenge the Chilean dictatorial regime through photographic images and those who experienced brutal repression during the Popular Revolt of October 2019 when attempting to document the crimes and human rights violations that were perpetrated during those days in the country.Although these are contexts with significant differences, these reprisals were systematic in each of the political scenarios proposed for this analysis: photographers were persecuted, beaten, tortured, mutilated, killed and even disappeared, in addition to suffering the destruction of their photographic material and equipment and veiling of their negatives.This article explores the survival strategies of images in the face of the photographic turn and the violence suffered by these groups recording their specific historical contexts. © 2024 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.